2010
DOI: 10.1111/j.1471-0374.2010.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐return experiences and transnational belonging of return migrants: a Dutch—Moroccan case study

Abstract: In this article we explore the links between return migration, belonging and transnationalism among migrants who returned from the Netherlands to northeast Morocco. While transnationalism is commonly discussed from the perspective of a receiving country, this study shows that transnationalism also plays a vital role in reconstructing post‐return belonging. Return migration is not simply a matter of ‘going home’, as feelings of belonging need to be renegotiated upon return. While returnees generally feel a stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 21 publications
(23 reference statements)
0
59
1
2
Order By: Relevance
“…It is therefore crucial to go beyond traditional approaches opposing integration and transnationalism, and recognise that return aspirations are multi -stranded, time -fluid, space -induced, and context -dependent. Return is thus a multifaceted phenomenon that encompasses a multiplicity of individual, family and structure--related motivations shaped by both spatial and temporal dimensions (Constant & Massey, 2002;De Bree, Davids & De Haas, 2010;De Haas & Fokkema, 2010).…”
Section: From Aspirations To Realisations: Placing Space and Timementioning
confidence: 99%
“…It is therefore crucial to go beyond traditional approaches opposing integration and transnationalism, and recognise that return aspirations are multi -stranded, time -fluid, space -induced, and context -dependent. Return is thus a multifaceted phenomenon that encompasses a multiplicity of individual, family and structure--related motivations shaped by both spatial and temporal dimensions (Constant & Massey, 2002;De Bree, Davids & De Haas, 2010;De Haas & Fokkema, 2010).…”
Section: From Aspirations To Realisations: Placing Space and Timementioning
confidence: 99%
“…their parents, sisters, brothers, and children when they move to the homeland. Although other studies (e.g., Conway and Potter 2009;De Bree, Davids, and de Haas 2010) have shown that this created a different type of transnationalism after return and influenced postreturn adjustment in the homeland, for the Adyge-Abkhaz diaspora the visits to the diaspora settlements have a political, social, and cultural meaning. For some, the repeated visits can be explained through transnationalism as a result of increased and cheaper transportation.…”
Section: Creating New Boundaries and Belongingsmentioning
confidence: 99%
“…Although the deportees I studied were primarily male not female, they too rely heavily on transnational material and affective ties. Scholars have found that return migrants use transnational strategies to gain social status (Goldring 1998) and to create a sense of belonging on returning home (de Bree et al 2010). The shame associated with deportation means that transnational ties do not bring social status to deportees.…”
Section: © 2013 the Author(s)mentioning
confidence: 99%
“…The relative rarity of habitual transnationalism raises the question of why only some migrants use transnational strategies. Transnational practices refer to cross-border practices and include activities that literally and symbolically cross national borders, meaning that migrants need not travel to participate in them (de Bree et al 2010). This is pertinent for deportees, whose international travel is often greatly restricted.…”
Section: © 2013 the Author(s)mentioning
confidence: 99%